The targetable kinase PIM1 drives ALK inhibitor resistance in high-risk neuroblastoma independent of MYCN status - Ricky M. Trigg (Nature Portfolio, 2019)
Anaplastic lymphoma kinase (ALK) inhibitors are currently being considered in neuroblastoma (NB), but its acquired resistance is reported in non-small cell lung cancers. Here, the authors have found PIM1 overexpression decreases sensitivity to ALK inhibitors in NB and combined ALK and PIM1 inhibition enhances anti-tumour efficacy in vitro and in PDX models.